Immune system effectors as biomarkers of prognosis after acute burns in a case-control study - Ferrari, Alejandro (2024)
Burns are a global health problem due to frequent complications, which lead to systemic inflammation, acute respiratory distresssyndrome, multiorgan dysfunction, and death. Following the initial injury, it has been demonstrated that the immune system plays akey role in early inflammation, tissue regeneration, and the response against pathogens. In this study, the performance of laboratorydeterminations as biomarkers of prognosis in acute burned patients was evaluated in a retrospective case-control protocol.Laboratory determinations were immunoglobulin G (IgG), immunoglobulin M (IgM), C-reactive protein (CRP), complement C4protein (C4), total serum protein (TP), albumin, prealbumin, cholesterol (CHOL), pseudocholinesterase activity (CHE), andtransferrin. Patients in the deceased group (DG) showed lower initial IgG levels (p < 0.05) than patients in the survivor group (SG),with a negative predictive value (NPV) of 0.86, and this difference persisted during the hospitalization period. Furthermore, DGpatients showed a decrease in CHOL and CHE during the hospitalization period (NPV of 0.86), a tendency that was not observed forthe SG. Albumin, TP, C4, and transferrin showed lower initial values in DG than the SG, with a strong correlation with the totalburned surface area (TBSA). These results indicate that IgG, CHOL, and CHE measurement might provide useful information formedical intervention independently of the TBSA and suggest that the measurement of TBSA-linked parameters might help toestimate the severity of burns more objectively. In this paper, the causes and implications of the alteration of effector molecules ofthe immune system are discussed.